Virtual Nurse for Detecting Suicide Risk Behaviors in Adolescents - Tarigan, Yohanes Zenriano; Kusumaningtiyas, Dwi Prima Hanis (Babali Publisher, 2024)
Introduction: Suicide is a complex phenomenon that is intriguing to study because its causes are still not fully understood. This phenomenon often garners media attention, as the number of incidents has significantly increased. Suicidal ideation frequently occurs in teenagers, and many who seek consultation report similar thoughts or engage in self-harm. The approach to problem-solving proposed in this research is the use of a virtual nurse as an early detection service for suicide risk behavior. A Virtual Nurse is an artificial intelligence-based application or system designed to provide health services and psychological support, particularly for teenagers. The Virtual Nurse uses machine learning algorithms to analyze user behavior, speech patterns, and interactions to identify signs of suicide risk. This study aims to analyze the effectiveness of the Virtual Nurse in detecting suicide risk behavior in adolescents. Method: This research utilized a pre-experimental design with a one-shot case study approach. Results: The implementation of the virtual nurse application for the detection of suicide risk behavior in adolescents over four weeks yielded favorable outcomes for 116 students (16%), while 74 students (39%) were categorized as showing poor results and the score for using virtual nurse in detecting suicide risk was 84 points. The result was that virtual nurse were classified as good in detecting suicide risk behavior in adolescents. Conclusion: The virtual nurse is an artificial intelligence-based application or system designed to provide psychological services and support to its users, particularly teenagers.